Pre-Irradiation of Boric Acid Solutions in a Research Reactor - Im, Hee-Jung; Tack Hong, Sung; Han, Gee-Yang; Chon Choi, Ke; Yeon, Jei-Won; Kim, Hung-Woo; Cho, Man-Soon; Jang, Kyung-Duk; Jae Park, Ul; Park, Sang-Jun; et al. (Asian Journal of Chemistry, 2013)
Interpretation of coolant chemistry performance is very important because the performance can be an effective indicator in monitoring operational safety of nuclear power plants. To determine the radiolysis degree of boric acid solutions, which are added for neutron absorption to control core reactivity during the nuclear power plant operation, and understand the physico-chemical nature of the process under neutron irradiation in a nuclear reactor, the preparation and safety check points for the irradiation of boric acid solutions are discussed.